THE SPECIFICS OF THE DIGITAL ACTIVITY OF REGIONAL DNIPRO TELEVISION - Shelefontiuk, Anna (International Journal of Innovative Technologies in Social Science, 2021)
According to the theory of Boczkowski-García-Perdomo, the specificity of the digital activity of regional television is analyzed. The trends inherent to digital regional TV journalism are first identified as global, and then they are analyzed in detail on material of the three TV channels of the city of Dnipro, Ukraine. We choose three TV channels for the analysis: “UA: DNIPRO”, “34 channel” and “Vidkrytyy”. The choice of channels stems from the fact that "UA: DNIPRO" and "34 Channel" have a long history of operation, steady TV audiences and a certain reputation in the regional media space of Dnipropetrovsk region. These channels began their activities in traditional, broadcast TV journalism, which is considered the main one for them. Digital practices are being introduced into the news production process in parallel with the main activity. The “Vidkrytyy” is a channel created less than 5 years ago from scratch as a private one. The newsroom first launched the website, then they started the online broadcasting, and only over time, the broadcast on the city's cable networks was launched. Thus, digital journalism has been and remains an important component of the channel's television activities. The conclusions confirm the fact that the chosen theory cannot be used without taking into account the specifics of the media sector.